Glossaire sumérien–français - Attinger, Pascal, 1952- (Wiesbaden)
1307 sayfa
Keywords: “The Glossaire sumérien–français, principalement des textes littéraires paléobabyloniens (Sumerian – French Glossary, Primarily Based on Old Babylonian Literary Texts) endeavours to fill one of the most glaring gaps in modern Sumerology by providing a much-needed printed glossary that satisfies scientific standards. The œuvre does not strive for completeness but offers an expansive choice of words taken from Old Babylonian literary texts from the beginning of the 2nd millennium BCE. Particular attention has been paid to (idiomatic) expressions of the type ‘noun (+ noun) + verb’ such as si “horn” + gu3 “voice” + ra “to beat” = “to sound the horn.” More than one thousand of such expressions have been registered. In more than 3.800 lexicographical notes, some of which extensive, Pascal Attinger clarifies the reading of difficult lexemes, discusses the meaning of rare or unclear terms and provides a detailed bibliography which will facilitate further research. The glossary itself is preceded by a catalogue of cited compositions including abundant bibliographical references and, where applicable, information on new duplicates, a comprehensive discussion of the importance of a consistent transliteration, as well as a concordance of common readings and those adopted in the Glossary” --